Analisis Resepsi Anggota Karang Taruna Resonda Tebet Mengenai Edukasi Seks dalam Film Dua Garis Biru - Aditya Darwanto; Syaifuddin (UNIVERSITAS KALBIS, 2022)
The rise of cases of adolescents in Indonesia who are pragment out of wedlock, it can happen of lack of education about sex. The purpose of this research is to discover audience reception (member of karang taruna RESONDA in Tebet) in interpreting the massage regarding promiscuity in Dua Garis Biru movie. The research uses encoding-decoding theory by Stuart Hall. Paradigm of this research is constructivisme with qualitative apporoach. Prominent Technique used in acquiring the data is by intimate interview. The researcher uses Stuart Hall, three categories of audience reception; Dominant Hegemony, Negotiation, and Opposition. The result off the research shows informant which is categorized in Dominant Hegemony acquired the massage of this movie such as information and new experience in accord to relationship of opposite gender. All informant admitted that they received a brand new information related to the effect of promiscuity. Informant which is categorized as Negotiation received positive aspect of this movie regarding sex education and informant, however not all of them like the movie, some of them are not fond of exaggerating style in dating. Informant which is categorized as Opposition refused all sorts of promiscuity, like any couple who surpass the norm in term of dating which does result pregnancy in teenager age.